Field management of anthracnose of chilli (Capsicum annuum) caused by Colletotrichum capsici - UTPAL DEY*, H.N. KAMBLE, D.N. DHUTRAJ and (Indian Phytopathology, 2015)
A field experiment was conducted to evaluate fungicides, bioagents and botanicals in-vivo during rabi, 2011-12 and kharif, 2012-13 to manage anthracnose caused by Colletotrichum capsici on chilli (Capsicum annuum L.) at Parbhani. All the treatments could effectively reduce the incidence, intensity and coefficient of disease index (CODEX) of anthracnose. Among fungicides, propiconazole (@ 0.1%) recorded least mean disease incidence, intensity, CODEX and increased dry pod yield over the control. The second best fungicide was hexaconazole (@ 0.1%), followed by carbendazim 12% + mancozeb 63% WP (@ 0.1%), captan (@ 0.25%) and copper oxychloride (@ 0.25%). The Trichoderma viride as a bioagent, and Allium sativum as a botanical could also effectively manage anthracnose. Further, economics [cost: benefit ratio] of all the treatments revealed highest monetary gain in hexaconazole (1:48.43), followed by propiconazole (1:25.68) and copper oxychloride (1:20.00). All the treatments significantly increased dry pod yield, with maximum gross and additional income over the control.